The type 1 insulin-like growth factor receptor is over-expressed in bladder cancer. - Rochester, M; Patel, N; Turney, B; Davies, DR; Roberts, I; Crew, J; Protheroe, A; Macaulay, V (2007)
OBJECTIVE: To analyse bladder cancer biopsies and investigate the pattern of expression of the type 1 insulin-like growth factor receptor (IGF1R), a receptor tyrosine kinase that mediates tumour cell proliferation, motility and protection from apoptosis. MATERIALS AND METHODS: Formalin-fixed specimens of bladder cancer (40 whole-mount, 80 cores on a tumour microarray) and normal bladder (15 samples) were stained immunohistochemically for the IGF1R. The IGF1R expression was also measured by quantitative reverse transcription-polymerase chain reaction (Q-RT-PCR) on RNA extracted from fresh frozen bladder cancers (61) and benign bladder (12). RESULTS: Of the 15 samples of normal bladder, 14 showed negligible (1+) or light (2+) IGF1R immunostaining. By contrast moderate (3+) or heavy (4+) staining for IGF1R was detected in 89 (74%) of the 120 samples of malignant urothelium. Q-RT-PCR showed significantly higher levels of steady-state IGF1R mRNA in tumours (all cases, Ta-T4) than in normal bladder (P < 0.05), indicating up-regulation at the transcriptional level. This difference was particularly evident when comparing normal urothelium with superficial (Ta-T1) or invasive (T2-4) tumours; only the latter showed significant IGF1R over-expression at the RNA level (P < 0.05 vs normal bladder). CONCLUSION: The IGF1R is up-regulated in bladder cancer compared with non-malignant bladder, and might contribute to a propensity for invasion.